Efficient bioconversion of enzymatic corncob hydrolysate into biomass and lipids by oleaginous yeast Rhodosporidium paludigenum KM281510 - Thanongsak Chaiyaso (2019)
© 2019, © 2019 Taylor & Francis Group, LLC. This study aims to valorize of enzymatic corncob hydrolysate (ECH) for biomass and lipid productions via microbial bioconversion by the efficient oleaginous yeast Rhodosporidium paludigenum KM281510. Biomass (5.63 g/L), lipids (3.29 g/L), and lipid content (58% (g/g)) were observed by batch cultivation in shaking flask. The effect of total sugar concentration in ECH, agitation rate, temperature, and initial pH were investigated in both batch and fed-batch cultivations by shaking flask and 3.0 L airlift bioreactor. Biomass, lipids, and lipid content of 27.77 g/L, 20.27 g/L, and 70% (g/g) were obtained with 100 g/L total sugar (68 g/L glucose, 29 g/L xylose, and 3 g/L arabinose), pH 6.5, 25 °C, 6.0 vvm, for 7 days by batch cultivation in bioreactor. Surprisingly, production parameters were improved by fed-batch, wherein these promising high biomass (36.06 g/L), lipid production (25.12 g/L), and lipid productivity (2.52 g/L/d) values were achieved. Moreover, fed-batch cultivation promoted the utilization of xylose (2.5-times) and arabinose (3.4-times) higher than batch cultivation, achieving lipid content (70% (g/g)) with oleic acid (53%). These results would be helpful for understanding the comprehensive utilization of ECH, especially the pentose sugars, for growth and lipogenesis of oleaginous yeast as well as being a qualified biodiesel feedstock.